Self-Reported Stress, Trauma, and Prevalence of Laryngoresponders in the General Population. - Helou, Leah B.; Welch, Brett; Hoch, Sarah; Gartner-Schmidt, Jackie (Journal of Speech, Language & Hearing Research, 2023)
Introduction: It has been proposed that some individuals are “laryngoresponders” (LRs) in that their stress manifests in the laryngeal region and laryngeal functions (e.g., voice and breathing). Preliminary data support the notion that LRs might differ from nonlaryngoresponders (NLRs) in their self-reported past trauma and recent stress. The purpose of this study was to establish the point prevalence of self-identified LRs in the general population. Method: Using a web-based questionnaire, participants reported up to 13 stressvulnerable bodily regions and described symptom nature and severity for each region. At the end of the questionnaire, they were explicitly prompted to report whether their laryngeal region or its functions were affected by stress. Participants were categorized a posteriori as Unprompted LRs, Prompted LRs, Inconsistent LRs, or NLRs. We compared LR and NLR groups on the Perceived Stress Scale (PSS-10) and the Childhood Trauma Questionnaire (CTQ-SF). We also redistributed the survey to a subset of participants to establish grouping reliability. Results: A total of 1,217 adults responded to the survey, and 995 provided complete data sets. Of those, 15.7% were classified as Unprompted LRs, 26.7% as Prompted LRs, 3% as Inconsistent LRs, and 54.6% as NLRs. Unprompted LRs demonstrated significantly higher/worse PSS-10 and CTQ-SF scores than all other groups. Reliability of LR classification was moderate upon follow-up, κ = .62, 95% confidence interval [0.47, 0.77]. Conclusions: Unprompted LRs described their symptoms in ways that were indistinguishable from patients with functional voice disorders (e.g., throat clenches, voice gets tired easily, lose my voice, voice gets hoarse). The method of self-report solicitation impacted the resulting response. Specifically, the report of larynx-related symptoms differed substantially depending on whether or not the participants were directly prompted to consider the larynx and its related functions.